BETWEEN FAITH AND FREEDOM: The Qur’an and the Childfree Lifestyle - Qibtiyah, Maria; Badruzaman, Abad (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2025)
This article deals with the childfree lifestyle through the lens of the Qur’an, a topic that has recently become controversial in Indonesia. Public opinion is divided: supporters argue that choosing not to have children is a matter of personal freedom, while opponents claim it contradicts social and religious expectations that married couples should try to have offspring. Using Gadamer’s hermeneutical perspective alongside Qur’anic interpretation, the article highlights several verses that encourage procreation—such as calls to increase descendants, praise for having noble offspring, and descriptions of children as a source of reward in the afterlife. These verses suggest that Islam generally discourages couples from intentionally avoiding children. However, the study also emphasizes that Qur’anic meaning is dynamic and must continually engage with contemporary realities, including the childfree trend. In this light, the childfree choice is explicitly forbidden but may be considered acceptable when supported by reasonable motives and when it contributes to personal or social benefit. This approach allows Islamic teachings on family and lineage to be understood in dialogue with contemporary realities.